Beneš 1931. évi terve és a magyar külpolitika válasza - Gulyás, László (Közép-Európai Közlemények, 2015)
Between the two world wars Hungarian-Czechoslovak relations were as cool as possible. It was Czechoslovakia among our neighbours whom we were in the worst terms with, having an atmosphere of mutual coldness and mistrustfulness. From signing the peace treaty of Trianon (1920) to the collapse of Czechoslovakia (1939) the two states were permanently fighting fierce diplomatic struggles. This permanent strife was only interrupted by few attempts to settle the affairs. We examine one of these attempts. In 1930 the Czechoslovak minister of foreign affairs, Edvard Benes elaborated an economic plan that included Hungary with a significant role. In our study we present this plan and the Hungarian response.